Effects of Fruit Coatings, Fungicide, and Storage Temperature on Fruit Shelf-Life and Qualities of ‘California’ Papaya - Widodo, Soesiladi Esti; Dirmawati, Suskandini R.; Zulferiyenni, Zulferiyenni; Wardhana, Rachmansyah A.; Fitria, Fitria; Fitri, Annisa; Fajryah, Jeanette (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
‘California’ papaya is a newly released papaya cultivar in Indonesia that has a very short shelf-life. Increasing demands in both local and export markets warrant the need for a proper postharvest technology to prolong its shelf-life. This research was conducted to study the effects of fruit coatings (chitosan, KD-112, plastic wrapping), fungicide Prochloraz, and storage temperatures on its fruit shelf-life and quality. Three parallel experiments were conducted with treatments arranged in a completely randomized design of a 2 x 2 x 2 factorial design.  The first factor was chitosan (with and without 1.25% chitosan), or KD-112 (with and without 14% KD-112), or plastic wrapping (with and without one layer plastic wrapping), the second was Prochloraz (with and without 0.67 mL/L Prochloraz), and the third was storage temperature (27-28 and 16-18 ºC). While Prochloraz did not affect fruit variables, cooler temperature and coatings lengthened fruit shelf-life with the best effect shown by plastic wrapping which lengthened fruit shelf-life by 13 days, without affecting fruit qualities. Significant effects of coating and cooler temperature determined their combined effects, with the best effect achieved by applying the three factors that lengthened fruit shelf-life by 11-23 days longer.